Human and machine hearing : extracting meaning from sound - Lyon, Richard F. (Cambridge : Cambridge University Press, 2017)
Human and Machine Hearing is the first book to comprehensively describe how human hearing works and how to build machines to analyze sounds in the same way that people do. Drawing on over thirty-five years of experience in analyzing hearing and building systems, Richard F. Lyon explains how we can now build machines with close-to-human abilities in speech, music, and other sound-understanding domains. He explains human hearing in terms of engineering concepts, and describes how to incorporate those concepts into machines for a wide range of modern applications. The details of this approach are presented at an accessible level, to bring a diverse range of readers, from neuroscience to engineering, to a common technical understanding. The description of hearing as signal-processing algorithms is supported by corresponding open-source code, for which the book serves as motivating documentation.
Theories of hearing -- On logarithmic and power-law hearing -- Human hearing overview -- Acoustic approaches and auditory influence -- Introduction to linear systems -- Discrete-time and digital systems -- Resonators -- Gammatone and related filters -- Nonlinear systems -- Automatic gain control -- Waves in distributed systems -- Auditory filter models -- Modeling the cochlea -- The CARFAC digital cochlear model -- The cascade of asymmetric resonators -- The outer hair cell -- The inner hair cell -- The AGC loop filter -- Auditory nerve and cochlear nucleus -- The auditory image -- Binaural spatial hearing -- The auditory brain -- Neural networks for machine learning -- Feature spaces -- Sound search -- Musical melody matching -- Other applications.
Title from publisher's bibliographic system (viewed on 04 May 2017).
Keywords: Hearing; Auditory perception -- Mathematical models; Auditory perception -- Computer simulation